Quinoa for Marginal Environments: Toward Future Food and Nutritional Security in MENA and Central Asia Regions - Choukr-Allah, Redouane; Rao, Nanduri K.; Hirich, Abdelaziz; Shahid, Mohammad; Alshankiti, Abdullah; Toderich, Kristina; Gill, Shagufta; Butt, Khalil Ur Rahman (Frontiers in Plant Science, 2016)
Quinoa is recognized as a crop of great value in terms of tolerance to abiotic stresses and there is growing interest to introduce it in marginal agricultural production systems worldwide. Also, quinoa is one of the most nutritious food crops currently known and the nutritive properties of the crop are seen as a means to fight malnutrition globally. Various quinoa cultivars have been screened for tolerance to salinity, water-use efficiency and nutritional quality and the positive attributes found in them have created even wider global interest in its cultivation. This paper summarizes 15 years of studies on assessing the potential for introducing the crop in a few countries of the Middle East and North Africa (MENA) and Central Asia regions and describes the key constraints for scaling-up the production under marginal growing conditions in the newly introduced countries.